Northern light or out in the cold : comparison of two Nordic regions - Ylinenpää, Håkan; Lundgren, Nils-Gustav (Luleå tekniska universitet, Innovation och Design, 1998)
The development of regions has attracted substantial interest during the recent decades, involving several studies of ‘industrial districts', ‘developing regions', ‘hi-tech regions' and ‘entrepreneurial districts'. Different propositions regarding how the development of dynamic regions can be understood has thus, with different theoretical approaches, been put forward. This article aims to increase our knowledge about how the factors behind the development of regions can be understood. The point of departure is Porter's ‘Diamond Model', which is applied as a theoretical framework for an analysis of two Nordic regions: The Oulu region (the city Oulu and the county of Pohjois Pohjanmaa) in northern Finland and the Luleå region (the city of Luleå and the county of Norrbotten) in northern Sweden. By utilising different data sources, interviews with key actors in the two regions as well as statistical data and previous studies, the study identifies four main factors behind the notably more favourable development of the Oulu region. These factors relate to the two cities' different positions in their national hierarchy of cities, different modes of co-operation between local and regional key actors, different roles as demanding customers played by the dominant companies in the regions, and structural differences regarding the role of emerging versus mature industries. Also factors with minor and often indirect importance for explaining occurring differences are identified in the article. Godkänd; 1998; 20071127 (ysko)